ANALYSIS OF THE PERFORMANCE EVALUATION OF THE LOGISTICS EXPRESS LINER PORT ON THE T-14 TANJUNG PERAK – LARANTUKA – LEWOLEBA – KALABAHI ROUTE IN REDUCING PRICE DISPARITY - Mawikere, William Aldrian Imanuel; Herijanto, Wahju (Institut Teknologi Sepuluh Nopember, 2023)
The express liner program also known in Indonesia as